Data about Long-eared owl Asio otus diet in a winter roost in Imperia (Western Liguria, North Italy) and notes on their activity cycle. - GALLI, LORIS; Daniele, Baroni; Ilaria, Gelli; Silvia, Launo; Claudio, Puppo; Riccardo, Rossi (country:ITA, 2015)
A Long-eared Owl Asio otus winter roost in Imperia town (Liguria, NW-Italy) have been studied since 2003. We’ve observed that a few tenth of owls every year occupy 4 nearby trees (2 Pinus pinea, 1 Pinus canariensis and 1 Ceratonia siliqua) from October to March (with a seasonal peak of more or less 50 individuals in December and January). All the owls in the evening leave the roost during a time range normally shorter than 30 minutes, with a peak of departures 27 ± 5.3 minutes after the sunset. In the morning they seem to arrive at the roost again during a short interval at dawn, mainly from the NW quadrant. Their flying direction lay in the NW quadrant towards the fields surrounding the town. A sample of 720 pellets and 17 prey remnants masses collected under the roost trees have been analysed giving us some insight about the wintering owls diet. Globally 1020 preys have been isolated. Mammals (nearly exclusively Apodemus sylvaticus and Rattus rattus) prevail in biomass (74.1 % of the whole), while Birds (mainly Sylvia atricapilla and Fringilla coelebs) result numerically dominants (63.4 %).